The Contribution of Saudi Arabian Scholars to the Literature on COVID-19: A Bibliometric Study. Issue 3 (3rd July 2022) - Al-Duwaish, Abdulaziz; Shehata, Ahmed; Farrag, Abdelrahman; Alshara, Mohammed; Eldakar, Metwaly; Al-Hugail, Abdul Karim
ABSTRACT: The purpose of the paper is to report the findings of Saudi researchers' academic performance on the topic of COVID-19. In addition, the paper explored the contribution of Saudi Arabia in the area and how Saudi Arabia is doing compared to other Arab countries The study adopted bibliometrix R to map the literature on the topic published by Saudi scholars. A total number of 3242 documents were retrieved from the Web of Science database and examined Using the software to mine information about journals, articles, authors, citations, keywords and countries. The analysis revealed that Saudi scholars had published a fair amount of COVID-19 studies in a small timespan. Scholars from Saudi Arabia have initiated a strong collaboration with other researchers worldwide. The data revealed that Saudi scholars have collaborated with scholars All over the world. Overall, Saudi Arabia had its share of global contribution on the subject (19 th place). Contribution from Saudi Arabia was found to be affiliated to other countries, especially the USA and Egypt The study focused only on Saudi scholars' productivity in the field of COVID-19. More research needs to be done in order to find how Arab scholars are progressing with COVID-19 research. Additionally, the study only used the Web of science to retrieve the data. Using Scopus might give us more understanding of the scholars' productivity in the field. Despite several studies on the field, this is the first study covering scholars' productivity in covid-19 in the Middle east. The results of the study are hoped to help in understanding the research progress in this area and how scholars collaborate in COVID-19 research.